THE ROLE OF COMPETENCE IN DRIVING BUSINESS FORWARD: BIBLIOMETRIC ANALYSIS USING SCOPUS DATABASE - Harva, Zahra Berlianda; Rahmawan , Muhammad Diandra; Susanty , Ade Irma (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This This study aims to explore and analyze research trends related to competence in business, particularly within the context of small and medium-sized enterprises (SMEs), using a bibliometric approach. Data was extracted from the Scopus database and visualized using VOSViewer, facilitating the identification of key research clusters, influential authors, and the relationships between various keywords within the domain. The findings reveal significant clusters centered around "competence," "innovation," and "business performance," highlighting the integral role of innovation in enhancing business competencies. Additionally, the analysis emphasizes the interconnectedness of human resource development and strategic business planning with competency development. This research contributes to a comprehensive understanding of the complexities in business competence studies and underscores the importance of a multidisciplinary approach in fostering sustainable business success. The results provide valuable insights for both researchers and practitioners in the field of business competence.